Pengaruh Pembelajaran Core (Connecting, Organizing, Reflecting, Extending) terhadap Pemahaman Konsep Mata Pelajaran IPAS Siswa Kelas V di MIS MMA 4 Sukabumi Bandar Lampung - Sari, Nur Rita; Latifah, Sri; Negara, Hasan Sastra (LPPM Institut Pendidikan Nusantara Global, 2025)
This study is motivated by the low level of students’ conceptual understanding, which is caused by the use of inappropriate learning models. This has led to students having difficulty understanding science concepts contextually in everyday life. To address this issue, the researcher implemented the CORE learning model (Connecting, Organizing, Reflecting, Extending) to improve students’ conceptual understanding. The purpose of this study is to determine the effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model on the conceptual understanding of IPAS (Social, Science, and Environmental Studies) among fifth-grade students at MIS MMA 4 Sukabumi, Bandar Lampung. This research uses a quantitative approach with a quasi-experimental method. The population consists of all fifth-grade students, totaling 55 students divided into two classes. The sampling technique used was cluster random sampling, with class 5A as the experimental group (26 students) and class 5B as the control group (29 students). The instrument used was a multiple-choice test of learning outcomes, which had been validated and tested for reliability. Data analysis was conducted using the Independent Samples t-Test to test the hypothesis. The test results showed a significance value (Sig. 2-tailed) of 0.004, which is less than the significance level of 0.05. This indicates that H0 is rejected and H1 is accepted. Therefore, it can be concluded that the use of the CORE (Connecting, Organizing, Reflecting, Extending) learning model has a significant effect on improving students’ conceptual understanding.